Bergson lu par Horkheimer - Jean-Baptiste Vuillerod (Recherches Germaniques)
In his first works, at the end of the 1920s and at the beginning of the 1930s, Max Horkheimer wrote some texts on Bergson’s philosophy of life, that reveal the importance of the French philosopher on his thought. This dialog with Bergson has often been overlooked, notably in the discussions on the Frankfurt School in France, possibly because some texts have not yet been translated into French. The aim of this article is thus to understand the Bergsonian influence on Horkheimer’s philosophy and on Critical Theory.